Gambaran Kista Dentigerous Gigi Premolar Rahang Atas pada Radiograf CBCT : Laporan Kasus - Gunawan Gunawan; Ivony Fitria (Andalas Dental Journal, 2021)
Background: Dentigerous cyst is a cyst that forms around the crown of an unerupted tooth. It begins when fluid accumulates in the layers of reduced enamel epithelium or between the epithelium and the crown of the unerupted tooth. Dentigerous cysts attach to the cementoenamel junction. Some dentigerous cysts are eccentric, developing from the lateral aspect of the follicle so that they occupy an area beside the crown instead of above the crown. In the case of dentigerous cysts with supernumerary, lesions appear to develop in the lateral aspect, so proper imaging is needed to see the expansion of the lesion. A modality that can be used to see the location and expansion of dentigerous cysts is by using a CBCT radiograph. Objective: Identification and interpretation of dentigerous cysts with supernumerary using CBCT radiography. Case Report: 12-year-old male came to the RSGM FKG Unpad bring a referral letter for CBCT photos. From the history it is known that the patient has a complaint of teeth that have not grown with swelling in the right maxilla. Case Management: Using CBCT, there were supernumerary and dentigerous cysts at 14,13. Sagittal, coronal and axial CBCT features show the position and condition of supernumerary, and give information about the location and expansion of dentigerous cyst at 14,13. Conclusion: CBCT provides a description of dentigerous cysts about location, lesion expansion, and involvement with surrounding tissue. CBCT provides an overview of lesions in sagittal, coronal and axial